The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.17509/ijal.v12i3.46231
|View full text |Cite
|
Sign up to set email alerts
|

The use of Jigsaw II technique in Malay grammar learning

Abstract: The Jigsaw II technique has been found to be effective in teaching and learning grammar based on cooperative learning. Therefore, this study was conducted to examine the effect of the use of the Jigsaw II technique on Form Four students’ attitudes and achievement in Malay grammar learning. Sixty-two students from two boarding schools in Kubang Pasu district, Kedah, Malaysia, were selected to participate in the study. They were divided into a treatment group and a control group. Thirty-one students of the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Thus, it gives good impact to students character later on. The result of the research also line with (Ahmad & Zainal, 2023) who analyzed about significant difference between achievement and attitudes of a students in learning grammar through Jigsaw II method. The research found that the student's attitude also influenced to students' achievement in learning grammar based on the Jigsaw II method.…”
Section: Introductionsupporting
confidence: 77%
“…Thus, it gives good impact to students character later on. The result of the research also line with (Ahmad & Zainal, 2023) who analyzed about significant difference between achievement and attitudes of a students in learning grammar through Jigsaw II method. The research found that the student's attitude also influenced to students' achievement in learning grammar based on the Jigsaw II method.…”
Section: Introductionsupporting
confidence: 77%